Archeomicrobiology applied to environmental samples. (June 2020) - Afouda, Pamela; Dubourg, Grégory; Raoult, Didier
Abstract: The study of ancient microorganisms represents one of the main ways to understand how microbes have evolved to date, especially those associated with humans or ecosystems of interest. However, these studies are always tedious because the viability of the microbes is difficult to maintain and the degradation of their DNA, can make their detection difficult. The explosion in the number of studies on ancient microorganisms in recent years is partly due to improved methods and their availability, ranging from microscopy to next generation sequencing techniques (NGS). In this article, we discuss these methods and their contribution to deciphering the ancient environmental microbial community, with particular emphasis on permafrost, ancient halite, amber and ancient rocks. Highlights: Ancient ecosystems contribute to the understanding of current ecology and microbial evolution. There are now several tools that provide different levels of information from observational studies to functional analyses. Retrieving genomic informations from these ancient ecosystem allow to assess the molecular clock of bacteria.